FKBP8 is a novel molecule that participates in the regulation of the autophagic pathway - Aguilera, Milton Osmar (2022)
Autophagy is a homeostatic process by which misfolded proteins, organelles and cytoplasmic material are engulfed in autophagosomal vesicles and degraded through a lisosomal pathway. FKBP8 is a member of the FK506-binding proteins family (FKBP) usually found in mitochondria and the endoplasmic reticulum. This protein plays a critical role in cell functions such as protein trafficking and folding. In the present report we demonstrate that the depletion of FKBP8 abrogated autophagy activation induced by starvation, whereas the overexpression of this protein triggered the autophagy cascade. We found that FKBP8 co-localizes with ATG14L and BECN1, both members of the VPS34 lipid kinase complex, which regulates the initial steps in the autophagosome formation process. We have also demonstrated that FKBP8 is necessary for VPS34 activity. Our findings indicate that the regulatory function of FKBP8 in the autophagy process depends of its transmembrane domain. Surprisingly, this protein was not found in autophagosomal vesicles, which reinforces the notion that the FKBP8 only participates in the initial steps of the autophagosome formation process. Taken together, our data provide evidence that FKBP8 modulates the early steps of the autophagosome formation event by interacting with the VPS34 lipid kinase complex. In this article, the protein FKBP38 is reported to be a novel modulator of the initial steps of the autophagic pathway, specifically in starvation-induced autophagy. FKBP38 interacts with the VPS34 lipid kinase complex, with the transmembrane domain of FKBP38 being critical for its biological function.